Unhealthy behaviours associated with uncontrolled hypertension among adults in India- Insights from a national survey - Kuppli Sai Sushma; Shubham Kumar; Chaitanya Gujjarlapudi; Vennam Bodhi Srividya; Madhur Verma; N. G. Nagamani; Kishore Yadav Jothula; Nidhi Jaswal; Sonu Goel (PLoS ONE, 2025)
Background Non-communicable diseases (NCDs) are governed by a cluster of unhealthy behaviours and their determinants, like tobacco and alcohol, unhealthy diet, lack of physical activity, overweight and obesity, pollution (air, water, and soil), and stress. Regulation of these unhealthy behaviours plays a crucial role in blood pressure control among individuals on hypertensive treatment, especially those suffering from uncontrolled hypertension. Hence, the present study aims at identifying the unhealthy behaviours associated with uncontrolled hypertension. Materials and methods We did a secondary data analysis of the National Family Health Survey (NFHS) -5 data (2019–2021). Among those taking prescribed medication to lower blood pressure levels, SBP ≥140 mm Hg or DBP ≥90 mm Hg were considered uncontrolled hypertension. The other socio-demographic variables and unhealthy behaviours were used as independent variables for analysis. Results The proportion of uncontrolled hypertension was 49·5% (95% CI: 45·5–53·4) and 36·8% (95% CI: 35.8–37.8) among males and females, respectively. Alcohol consumption, clean fuel usage, and high BMI (≥30kg/m2) were the behavioural characteristics significantly associated with uncontrolled hypertension among males. In contrast, tobacco usage, alcohol consumption, coverage by Health insurance, presence of Diabetes, heart disease, usage of clean fuel, and high BMI (≥30kg/m2) were the behavioural characteristics significantly associated with uncontrolled hypertension among females. Regression results portrayed that higher age groups (45 and above) have found higher odds for men (OR: 7.6, CI: 4.6–12.3) and women (OR: 6.08, CI: 4.0–6.0) compared with 30 years and below age groups. Similarly, higher odds were found among the wealthiest wealth quintile than the poorest wealth quintile among men and women. Conclusion The current study reported a high proportion of uncontrolled hypertension. Providing opportunistic health education during blood pressure monitoring, regular screening, and targeted interventions will not only help to reduce its prevalence but also reduce the risk of developing related health implications.